Fixed Orthodontic Appliance Associated With Change in Bacterial Diversity During First Stage of Active Orthodonotic Treatment - Ahmed S. Al-Janabi (Journal of Global Pharma Technology, 2016)
Background: some researchers have noted that fixed orthodontic appliance (FOA) have stirring on oral hygiene that lead to high cariogenic challenge. Moreover, based on the difficulty of maintaining oral hygiene, it can also affect germs under the gums by orthodontic devices, These variables would probably lead to the colonization of pathogenic bacteria, which are responsible for inflammation of the gingival, destruction of the periodontal support and changes in the enamel surface. Objective: Isolation and identification of bacteria among orthodonotic patients at progressive time during first stage of active orthodonotic treatment and molecular identification of highly cariogenic bacteria Streptococcus mutans as well as an in vitro evaluation of antibiotic sensitivity/resistance for bacterial isolates. Material and Methods: Sixty-five patients treated with fixed orthodontic appliance (FOA) their age between 12-25 years. Imprint swab samples were collected between brackets on the tooth surface monthly at zero day, 1st, 2nd and 3rd to be cultured aerobically and anaerobically. Bacterial isolated were identified in all age groups at progressive time. Molecular detection of S.mutans was performed using species specific primer Sm 479. The antibiotics sensitivity were done by use Kirby- Bauer disc diffusion method for bacterial isolates, the antibiotic selected was most common antibiotic used during orthodontic infection ( amoxicillin, amoxi-clav, cefotaxim, erythromycin and ciprofloxacin). Results: A total 186 bacterial isolates were obtained from 65 sample of tooth swabs in zero day (immediately after orthodontic device appliance) and 183 bacterial isolates were obtain at first month after wearing orthodontic device, while 195 bacterial isolates were obtained at second month after wearing the device, in the last visit (3rd month after put orthodontic device) 202 bacterial isolates were obtained, and all samples give positive bacterial culture as shows in table (2). Also the result shows that Staphylococcus spp. was the most bacterial isolates appear in patients with fixed orthodontic appliance (FOA). The study indicated neglected statistically significant difference over progressive time except alpha and beta streptococci and P.aurginosa according to Chi-square test. The bacterial isolated during this study include Staphylococcus (S. epidermidis and S.aurus), Lactobacillus spp., Streptococcus (alpha, beta, and gamma), E.coli, Klibsilla spp., Enterobacter spp., and P.aurginosa. Species specific primer Sm 479F/R using polymerase chain reaction (PCR) indicated that S.mutans was detected and increased from 60% at zero day to 80% at 3rd month. The antibiotic sensitivity test recorded that ciprofloxacin and amoxi-clav shows high effective against bacterial isolates. Conclusion: The studies conclude that oral cavity colonized by large number of microorganisms that contribute in infection during orthodontic treatment. Staphylococcus (aurus and epidermidis) was the most common bacteria isolated from patients during initial stage of orthodontic treatment which appear in (81.5%) of the total isolates followed by Lactobacillus spp. and then streptococcus spp. which appear non-statistically significant difference (p ≥0.05) among progress with treatment. The most common gram negative bacteria in zero day is E.coli (20%), Klibsilla (18%), Enterobacter spp.(20.8) while pseudomonas aeriginosa (10.6) and also shows non-statistically difference except P.aurginosa, The flora exists in harmony with the host but this relation may be broken due to orthodontic device. The molecular detection of S.mutans by species specific primer shows increase in percentage from 60% in zero days to 80% in third month. All gram positive showed high level of susceptibility to amoxi-clav followed by ciprofloxacin and cefotaxime while gram negative show high sensitive to erythromycin followed by ciprofloxacin and cefotaxime.Keywords: Fixed orthodontic appliance, Bacterial diversity, Antobiotic sensitivity, S. mutans.